Shaul Magid, Ed., and Jordan Gayle Levy, Trans. The Bible, the Talmud, and the New Testament: Elijah Zvi Soloveitchik’s Commentary to the Gospels - Sax, Benjamin E. (Studies in Christian-Jewish Relations, 2020)
No abstract is available.